Business Consulting en los procesos de almacén y distribución en la empresa HENTARI Perú S.R.L - Collantes Champi, Tatiana Margole (2024)
HENTARI PERU is a company that produces and markets over-the-counter medicines. The objective of the thesis is to propose an improvement in efficiency and productivity in its warehouses located in Ate Vitarte. During the period 2023 - 2024, a business consulting study was carried out in which documents were reviewed, interviews were conducted with key personnel, time recording and observation of processes. As a result of the investigation, it was evident that HENTARI PERU had high sales expenses, which were representative in the Warehouse and Distribution process. Through an analysis, it was concluded that the problem of strategic impact on the operational level was the high W&D expenses, which represented 4.19% in Peru with respect to sales and these in turn were above the average Latam expense (3.3%); impacting the strategic objective of the organization, which seeks to obtain an increase in operating profit by 7% by 2025, through the reduction of W&D expenses to 3.89%, through operational efficiency in the supply chain. Based on this problem, 5 projects are proposed: (i) Centralization of order deliveries to the province, (ii) Standardization of cases per pallet for deliveries in Lima, (iii) Dispatch of products through dry transport units, (iv) Online entry and digitalization of the process of entry, unloading and storage of products, (v) Chaotic Storage. All these proposals were implemented from July 2024, generating positive savings valued at US$96,867.74 for 2024 and US$283,380.91 for 2025. In addition, over a 5-year horizon, the projects have a positive NPV of US$845,120. On the other hand, from a social perspective, the projects are aligned with the organization's global CSR strategy, positively impacting the SDGs managed by the company, through the reduction of CO2 emissions, promoting decent work and gender parity. Finally, the savings obtained in W&D expenses strategically impact financial ratios, since they generate a 1.85% increase in operating profit for 2025, compared to the 7% set as a strategic objective.